The bovine immune response to Brucella abortus. III. Preparation of antisera against a Brucella component precipitated by sera of some infected cattle. - Stemshorn, B (1981)
Two methods are described for the partial purification of a high molecular weight, heat-resistant component (CO1) of sonicates of smooth and rough Brucella abortus which is precipitated by sera of some infected cattle. Method 1, a combination of gel filtration chromatography and polyacrylamide gel electrophoresis, was used to prepare CO1 from sonicates of a smooth field strain of B. abortus. Method 2, a combination of gel filtration chromatography and heat treatment, was used to obtain CO1, from sonicates of rough B. abortus strain 45/20. Rabbit antisera produced against CO1 prepared by either method contained only CO1 precipitins but were negative in standard agglutination and complement fixation tests conducted with whole cell antigens. Evidence is presented that CO1 is identical to Brucella antigen A2, and it is proposed that in future the designation A2 be employed.